The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species - Rosa, Paolo; Wei, Na-Sen; Xu, Zai-Fu (Zootaxa, 2016)
The Chinese Chrysis of the inaequalis species-group are revised and C. extraordinaria sp. nov. is described. Chrysis extraordinaria sp. nov. is recognisable by the following characteristics: mesopleuron tridentate, apex of T3 with six teeth, and T3 metallic blue, contrasting with T1 and T2 golden to metallic red. A modification to the species-group key by Kimsey & Bohart (1991) is proposed.